Photodegradation of aqueous diisopropanolamine using Cu/TiO2: Effect of calcination temperature and duration - Ramli, R.M. (Trans Tech Publications Ltd, 2014)
The effects of calcination temperature and duration during preparation of Cu/TiO2 photocatalyst were investigated. The photocatalysts were characterized using X-ray and BET specific surface area analyzer. It was observed that the temperature and duration during calcination process have a significant effect on the photocatalyst properties and photocatalytic activity. Optimum temperature and duration for the calcination of the synthesized photocatalyst were found to be at 450 Â°C and 1.5 h, respectively. Photodegradation study of aqueous diisopropanolamine solution (1000 ppm) using the prepared photocatalyst showed a significant COD removal under visible light irradiation. The photocatalyst calcined at optimum parameters gave the highest COD removal of 63. Â© 2014 Trans Tech Publications, Switzerland.